(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
Maqsud of Uzbek literature from one of the outstanding figures of Azerbaijan on October this is the eighth of a thousand years, he was born in the city of the seven third I can find. One thousand twenty-eighth year of the poet came in, live in the capital until the end of his life, and creativity. Know that it is a land of the second city. Maqsud of this “Jaloliddin Manguberdi” origin of the game and the game will go one word about the game to make it worthwhile too until now